Altered temporal connectivity and reduced meta-state dynamism in adolescents born very preterm. Issue 1 (7th February 2023) - Lahti, Katri; Setänen, Sirkku; Vorobyev, Victor; Nyman, Anna; Haataja, Leena; Parkkola, Riitta
Abstract: Adolescents born very preterm have an increased risk for anxiety, social difficulties and inattentiveness, i.e. the 'preterm behavioural phenotype'. The extreme end of these traits comprises the core diagnostic features of attention and hyperactivity disorders and autism spectrum disorder, which have been reported to show aberrant dynamic resting-state functional network connectivity. This study aimed to compare this dynamism between adolescents born very preterm and controls. A resting-state functional magnetic resonance imaging was performed on 24 adolescents born very preterm (gestational age <32 weeks and/or birth weight ≤1500 g) and 32 controls born full term (≥37 weeks of gestation) at 13 years of age. Group-wise comparisons of dynamic connectivity between the resting-state networks were performed using both hard clustering and meta-state analysis of functional network connectivity. The very preterm group yielded a higher fraction of time spent in the least active connectivity state in hard clustering state functional network connectivity, even though no group differences in pairwise connectivity patterns were discovered. The meta-state analysis showed a decreased fluidity and dynamic range in the very preterm group compared with controls. Our results suggest that the 13-year-old adolescents born very preterm differ from controls in the temporal characteristics of functional connectivity. The findings may reflect the long-lasting effects of prematurity and the clinically acknowledged 'preterm behavioural phenotype'. Abstract : Lahti et al . report diminished dynamics in brain functional connectivity studied with the functional MRI in resting state as a possible sign of long-lasting consequences of very premature birth on brain connectivity in 13-year-old adolescents compared to the term-born peers. Graphical Abstract: Graphical abstract